A study of substance abuse amongst a group of high school learners in the Eisleben (Botlokoa) area of the Limpopo Province - Rakubu, Kholofelo Annah (My University, 2007)
Refer to the document
Thesis (M.A. (Criminology)) -- University of Limpopo, 2007
Keywords: Substance abuse; Alcohol abuse; High school learners; Substance abuse -- South Africa; High school students -- Substance abuse -- South Africa